Modern options of endoscopic retrograde stenting of bile ducts in treatment of obstructive jaundice at malignant pancreatobiliary tumors - S. A. Budzinsky; S. G. Shapovalyants; Ye. D. Fedorov; A. G. Mylnikov; D. V. Bakhtiozina (Российский журнал гастроэнтерологии, гепатологии, колопроктологии)
Aim of investigation. Acute obstructive jaundice developed on background of malignant pancreatobiliary neoplasms is one of the most complex and dramatic problems of modern abdominal surgery. At surgical interventions at the climax of obstructive jaundice and/ or cholangitis, postoperative period of these patients is characterized by high severity and is accompanied by high postoperative mortality. Due to this in the last decades the increasing number of researchers prefer endoscopic retrograde approach of biliary drainage for treatment of obstructive jaundice.Material and methods. From January, 2007 to July, 2013 overall 3269 endoscopic retrograde interventions on major duodenal papilla (MDP) have been executed in the Scientific-educational center of abdominal surgery and endoscopy, Moscow city clinical hospital #31. Endoscopic stenting of biliary tract have been carried out in 523 cases, of them 418 (79,9%) procedures were carried out in 287 patients with jaundice of neoplastic origin (148 women, 139 men). Patients were in the age of 32 to 94 years (mean 68,2±9,3 year). With the help of the comprehensive diagnostic program providing ultrasound investigation, computer tomography, endoscopic ultrasonography and endoscopic retrograde cholangiopancreatography, it was possible to determine in 207 (72,1%) cases the distal block of biliary tract due to tumors of MDP, terminal CBD portion, distal part of common bile duct and pancreatic head, and the proximal block in 80 (27,9%) cases at lesions of gallbladder, hepatico-choledochal duct, lobar hepatic ducts or compression of proximal biliary tree by lymph nodes of hepatoduodenal ligament.Results. Bilioduodenal stents at 272 (94,8%) patients were installed after preliminarily endoscopic papillosphincterotomy (EPST). Adequate drainage of biliary tracts after biliary stenting was achieved in all patients. At the same time in 48 cases stenting of biliary tract failed. The reasons of failure were mainly due to duodenal stenosis caused by malignant involvement and extended and convoluted neoplastic deformation of the bile duct. Complications after endoscopic interventions, including acute pancreatitis, cholangitis, bleeding from EPST zone, perforation of wall of duodenum and stent migration, occurred in 22 cases (5,3%). Postoperative mortality was 3,5%. Thus almost in all cases death occurred after achievement of endoscopic biliary decompression. After bilioduodenal stenting in all patients jaundice was resolved or has essentially decreased. In 230 (80,1%) of them endoscopic aid was final treatment method of late-stage neoplastic process in inoperable patients. At relapse of jaundice endoscopic sanitation or stent replacement was performed. In other patients (19,9%) after resolution of jaundice surgical decompression interventions have been carried out.Conclusion. According to authors data, at malignant pancreatobiliary tumors in 85,7% of cases endoscopic retrograde drainage of the biliary tracts is possible and effective in treatment of obstructive jaundice. This method allows to prepare patients with obstructive jaundice for surgical interventions, including radical treatment, or may be a final method of treatment in inoperable patients. Morbidity rate after endoscopic retrograde interventions on MDP for acute obstructive jaundice of neoplastic origin is almost same as at those after standard retrograde interventions and according to our results equals to 5,3%.